The Department of Rare Books and Special Collections : a novel - Jurczyk, Eva (Poisoned Pen Press, 2022)
"Liesl Weiss has been (mostly) happy working in the rare books department of a large university, managing details and working behind the scenes to make the head of the department look good. But when her boss has a stroke and she's left to run things, she discovers that the library's most prized manuscript is missing. Liesl tries to sound the alarm and inform the police about the missing priceless book but is told repeatedly to keep quiet to keep the doors open and the donors happy. But then a librarian goes missing as well. Liesl must investigate both disappearances, unspooling her colleagues' pasts like the threads of a rare book binding as it becomes clear that someone in the department must be responsible for the theft. What Liesl discovers about the dusty manuscripts she has worked among for so long-and about the people who preserve and revere them-shakes the very foundation on which she has built her life"--